2020
DOI: 10.1126/sciadv.aay7505
|View full text |Cite
|
Sign up to set email alerts
|

Probing biophysical sequence constraints within the transmembrane domains of rhodopsin by deep mutational scanning

Abstract: Membrane proteins must balance the sequence constraints associated with folding and function against the hydrophobicity required for solvation within the bilayer. We recently found the expression and maturation of rhodopsin are limited by the hydrophobicity of its seventh transmembrane domain (TM7), which contains polar residues that are essential for function. On the basis of these observations, we hypothesized that rhodopsin’s expression should be less tolerant of mutations in TM7 relative to those within hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 40 publications
7
80
0
Order By: Relevance
“…4). These findings parallel recent investigations of the co-translational folding of rhodopsin, where it was found that its expression and trafficking were highly sensitive to mutations that alter the hydrophobicity of a polar transmembrane domain containing functionally constrained polar residues (48,49). However, the R231 mutations characterized herein demonstrate that the inefficiency of translocon-mediated membrane integration can cut both ways.…”
Section: Structural Basis For R231c Super-traffickingsupporting
confidence: 87%
“…4). These findings parallel recent investigations of the co-translational folding of rhodopsin, where it was found that its expression and trafficking were highly sensitive to mutations that alter the hydrophobicity of a polar transmembrane domain containing functionally constrained polar residues (48,49). However, the R231 mutations characterized herein demonstrate that the inefficiency of translocon-mediated membrane integration can cut both ways.…”
Section: Structural Basis For R231c Super-traffickingsupporting
confidence: 87%
“…We instead used a close proxy for MMR dysfunction, treatment with the purine analog 6-TG, which selectively enriches for MMR-defective cells which lack the ability to remove the resulting lesions. As with other deep mutational scans, these results may be further refined with orthogonal functional selections 62 , 90 or complemented by specialized assays for protein stability, 80 localization, 91 or partner (MSH6) binding. Finally, scaling this approach to genes longer than MSH2 may require alternative delivery strategies such as landing pads 92 , 93 to circumvent size limitations of lentiviral packaging.…”
Section: Discussionmentioning
confidence: 99%
“…within large data sets. 20,30 Using these ΔΔG values, we applied a series of increasingly stringent cutoffs to filter out neutral or stabilizing mutations and define subsets of TM7 variants that are enriched with destabilizing mutations. For both TM2 and TM7 variants, the rank correlation between temperatureand retinal-sensitivity improves as the stringency of the cutoff value increases (Table 1).…”
Section: Structural and Energetic Basis For The Coupling Between Tempmentioning
confidence: 99%
“…These compounds bind to the folded opsin apoprotein with high affinity 21 and form a covalent Schiff base with a conserved lysine (K296). Our investigations have collectively revealed that the plasma membrane expression (PME) of rhodopsin is particularly sensitive to mutations within its seventh transmembrane domain (TM7), 20 which is intrinsically prone to cotranslational misfolding. 19 Moreover, variants bearing mutations within TM7 appear to be less sensitive to the proteostatic effects of retinal relative to mutations within its second transmembrane domain (TM2), which is considerably more hydrophobic.…”
Section: Introductionmentioning
confidence: 99%